ANALISIS STRUKTUR MODAL PT BERLIAN LAJU TANKER TBK. PERIODE 2003-2016 (PERUSAHAAN PELAYARAN TERBESAR YANG HAMPIR BANGKRUT KARENA - Handoyo Widianto (Majalah Ilmiah Bahari Jogja, 2017)
This study examines the capital structure of PT Berlian LajuTanker Tbk. in period 2003-2016. The problem study is thedevelopment of capital structure of PT Berlian Laju Tanker Tbk. inperiod 2003-2016 that caused it almost went bankrupt.This research is quantitative descriptive. The data studied inthis research is secondary data. Data collection techniques used is documentation method with quantitative descriptive analysismethods.The research found that the capital structure of PT Berlian LajuTanker Tbk. in the period 2002-2016 was dominated by debt. This isindicated by the high ratio of DER (Debt to Equity Ratio) that is equalto 70.01%. The higher the ratio, indicating the greater the capitalderived from debt. Due to the high debt in the company's capitalstructure, the company is almost bankrupt in 2012 which is shownby the inability of the company to pay the debt. This event teachesthat firms that want to survive should pay attention to thecomposition of their capital structure remains healthy, ie notdependent on debt, but more use their own capital (equity).Keywords: Capital Structure, Shipping Company